Overview of the effect of rumen-protected limiting amino acids (methionine and lysine) and choline on the immunity, antioxidative, and inflammatory status of periparturient ruminants - Khan, Muhammad Zahoor; Liu, Shuai; Ma, Yulin; Ma, Mei; Ullah, Qudrat; Khan, Ibrar Muhammad; Wang, Jingjun; Xiao, Jianxin; Chen, Tianyu; Khan, Adnan; Cao, Zhijun (Frontiers in Immunology, 2023)
Overproduction of reactive oxygen species (ROS) is a well-known phenomenon experienced by ruminants, especially during the transition from late gestation to successful lactation. This overproduction of ROS may lead to oxidative stress (OS), which compromises the immune and anti-inflammatory systems of animals, thus predisposing them to health issues. Besides, during the periparturient period, metabolic stress is developed due to a negative energy balance, which is followed by excessive fat mobilization and poor production performance. Excessive lipolysis causes immune suppression, abnormal regulation of inflammation, and enhanced oxidative stress. Indeed, OS plays a key role in regulating the metabolic activity of various organs and the productivity of farm animals. For example, rapid fetal growth and the production of large amounts of colostrum and milk, as well as an increase in both maternal and fetal metabolism, result in increased ROS production and an increased need for micronutrients, including antioxidants, during the last trimester of pregnancy and at the start of lactation. Oxidative stress is generally neutralized by the natural antioxidant system in the body. However, in some special phases, such as the periparturient period, the animal’s natural antioxidant system is unable to cope with the situation. The effect of rumen-protected limiting amino acids and choline on the regulation of immunity, antioxidative, and anti-inflammatory status and milk production performance, has been widely studied in ruminants. Thus, in the current review, we gathered and interpreted the data on this topic, especially during the perinatal and lactational stages.